Town Planning Draft of Burkhard Christoph von Münnich (1727) for the Protection of Petersburg from Floods as a Monument of the Epoch of Peter I - Klimenko, Sergey V. (Actual Problems of Theory and History of Art, 2018)
The article considers the little-known draft for the protection of Petersburg from floods developed by military engineer B. C. von Münnich in 1727. This hydrotechnical draft has not yet occupied a worthy place in the architectural history of St. Petersburg, which can be explained by its specific purpose. The analysis of the Petersburg plan, presented with the system of protective constructions shown on it, is the goal of the article. This drawing is compared with the corpus of known plans of the city and the planning events of the Petrine time. In particular, an attempt was made to link the layout of the Admiralty Island depicted on the plan of Münnich with the settlement of this area in the first half of the 1720s under the leadership of N. F. Gerbel. Actually, engineering draft of B. C. von Münnich for the first time in the history of St. Petersburg offered a solution to the problem of flood protection throughout the town. Unlike the plan of St. Petersburg, the second part of the draft of Munnich has never been fully published. It is an album that includes the extensive explanatory text and drawings of hydraulic structures. Embankment river constructions designed by the engineer enabled the built up upper part of the roadway to be considerably lifted compared to the natural level of the banks. The new lines of embankments designed in the draft, which were simultaneous with dams, had a regular character, which presupposed the straightening of river banks. The draft of Münnich of 1727 should be regarded as a document that actually developed the plans of Peter the Great on the town planning development of St. Petersburg. In this respect, the document can be considered as a monument to the epoch of Peter I.